Learning Cycle 7E-Based Chemistry Learning: Its Impact on Grade X Students’ Achievement and Motivation - Eli Aprianingsih; Cinintya Ramanda (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to determine the effect of implementing the Learning Cycle 7E learning model on student learning outcomes and motivation in chemistry learning for class X, especially on the material of electrolyte and non-electrolyte solutions, and to compare its effectiveness with conventional learning models applied in schools. Methodology: The study used a quasi-experimental method with a posttest control group design. Samples were taken using a saturated sampling technique on grade X students of State Senior High School 1 Brang Rea. The research instruments included a learning motivation questionnaire and a learning outcome test on electrolyte-nonelectrolyte solutions. Data analysis used the Lilliefors, Kruskal-Wallis, Mann-Whitney normality tests, and IBM SPSS Statistics 22.0 software. Main Findings: The results of the study showed that the Learning Cycle 7E learning model did not have a significant effect on students' chemistry learning outcomes (sig. 0.392 > 0.05) or student learning motivation (sig. 0.386 > 0.05). Multivariately, the application of this model also did not show better effectiveness than conventional learning in improving the learning outcomes and motivation of class X students. Novelty/Originality of this study: The novelty of this research lies in the simultaneous analysis of the influence of the 7E Learning Cycle model on two important variables, namely the learning outcomes and motivation of 10th grade chemistry students on the topic of electrolyte and nonelectrolyte solutions.